Gender Specific Vulnerability in Climate Change and Possible Sustainable Livelihoods of Coastal People: A Case from Bangladesh - Garai,Joydeb (2016)
The paper addresses the gender specific vulnerability of coastal people in climatic hazards in Bangladesh. This study has been conducted by qualitative methods with some qualitative tools i.e. Key Informants Interview (KII) and Focus Group Discussion (FGD) to get the vivid and comprehensive views about gender specific susceptibility of climate induced hazards from social, gender, cultural and behavioral perspectives. The paper explores the gender specific vulnerability of climate change and possible sustainable livelihoods of coastal people in Bangladesh. This paper finds that climate change is not gender neutral. It affects men and women differently for their roles and responsibilities in the society. Womens roles are often confined to household labor such as looking after children and ailing people, as well as disaster specific roles such as saving properties from obliteration. These roles make women particularly vulnerable in natural hazards. By contrast, mens roles often include working outside and so are more likely to escape natural hazards. The paper also finds that womans dependency on natural resources is severely affected by climate change variability which causes vulnerability to women in natural hazards. This paper outlines key considerations of gender and climate change that can helps policy makers improve policy and implementation for the diminution of vulnerability of women in Bangladesh as well as developing countries of the world.